Rancang Bangun Alat Pendeteksi Kebugaran Paru-Paru Pada Personil TNI (Spirometer) Berbasis Arduino Uno - M. Sigit Purwanto; Yudi Hernawan; Lailatul Nahroni (Jurnal Teknik Elektro dan Komputer TRIAC, 2019)
The lungs is one of the important organs in the respiratory process in humans, especially TNI. If the lungs in the human body is impaired then it can cause dangerous diseases such as tuberculosis, bronchitis, and efisema. In its report, WHO (World Helth Organization) said that respiratory illness is the fourth most killer in the world. Research shows that lung health can be detected by measuring the volume of air capacity in the lungs. To measure the capacity of the air volume we can use a tool called Spirometer. Currently, health checks using Spirometer can only be done at the hospital. This is because the developed Spirometer is a Spirometer that is large and expensive so it is not possible to test using Spirometer every day. Because of this the author wants to research and develop a Spirometer that is easy to use anywhere, anytime, and by anyone. By utilizing simple physics laws such as bernoulli and continuity, the predicted volume capacity of Lung on Spirometer is close to the existing Spirometer.Keywords: Air volume capacity, Health, Lung, Spirometer.